Cellular Immunity of SARS-CoV-2 in the Borriana COVID-19 Cohort: A Nested Case-Control Study - Salvador Domènech-Montoliu; Joan Puig-Barberà; María Rosario Pac-Sa; Alejandro Orrico-Sanchéz; Lorna Gómez-Lanas; Diego Sala-Trull; Carmen Domènech-Leon; Alba Del Rio-González; Manuel Sánchez-Urbano; Paloma Satorres-Martinez; Laura Aparisi-Esteve; Gema Badenes-Marques; et al. (MDPI AG, 2024)
Our goal was to determine the cellular immune response (CIR) in a sample of the Borriana COVID-19 cohort (Spain) to identify associated factors and their relationship with infection, reinfection and sequelae. We conducted a nested case-control study using a randomly selected sample of 225 individuals aged 18 and older, including 36 individuals naïve to the SARS-CoV-2 infection and 189 infected patients. We employed flow-cytometry-based immunoassays for intracellular cytokine staining, using Wuhan and BA.2 antigens, and chemiluminescence microparticle immunoassay to detect SARS-CoV-2 antibodies. Logistic regression models were applied. A total of 215 (95.6%) participants exhibited T-cell response (TCR) to at least one antigen. Positive responses of CD4+ and CD8+ T cells were 89.8% and 85.3%, respectively. No difference in CIR was found between naïve and infected patients. Patients who experienced sequelae exhibited a higher CIR than those without. A positive correlation was observed between TCR and anti-spike IgG levels. Factors positively associated with the TCR included blood group A, number of SARS-CoV-2 vaccine doses received, and anti-N IgM; factors inversely related were the time elapsed since the last vaccine dose or infection, and blood group B. These findings contribute valuable insights into the nuanced immune landscape shaped by SARS-CoV-2 infection and vaccination.